Master plan project for Vietnam fisheries : (Consulting Engineering and Planners AS, 1996)
A major development problem is related to the supply of rural citizens in remote mountainous provinces, who suffer from malnutrition. the growth incom will allow the urban consumers to invest in household storage capacity for frozen fish and meat.